Mechanism of Photosignaling by Drosophila Cryptochrome: ROLE OF THE REDOX STATUS OF THE FLAVIN CHROMOPHORE. - Ozturk, N.; Selby, C.P.; Zhong, D.; Sancar, A. (Journal of Biological Chemistry, 2014)
Cryptochrome (CRY) is the primary circadian photoreceptor in Drosophila. Upon light absorption, dCRY undergoes a conformational change that enables it to bind to Timeless (dTIM), as well as to two different E3 ligases that ubiquitylate dTIM and dCRY, respectively, resulting in their proteolysis and resetting the phase of the circadian rhythm. Purified dCRY contains oxidized flavin (FADox), which is readily photoreduced to the anionic semiquinone through a set of 3 highly conserved Trp residues (Trp triad). The crystal structure of dCRY has revealed a fourth Trp (Trp-536) as a potential electron donor. Previously, we reported that the Trp triad played no role in photoinduced proteolysis of dCRY in Drosophila cells. Here we investigated the role of the Trp triad and Trp-536, and the redox status of the flavin on light-induced proteolysis of both dCRY and dTIM and resetting of the clock. We found that both oxidized (FADox) and reduced (FAD) forms of dCRY undergo light-induced conformational change in vitro that enable dCRY to bind JET and that Trp triad and Trp-536 mutations that block known or presumed intraprotein electron transfer reactions do not affect dCRY phototransduction under bright or dim light in vivo as measured by light-induced proteolysis of dCRY and dTIM in Drosophila S2R+ cells. We conclude that both oxidized and reduced forms of dCRY are capable of photosignaling.